IMPLEMENTASI MODEL ROLEM DAN SELF EFFICACY SERTA DAMPAKNYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - ALHAQ, ARINI; JL, ANA RISQA; AMBARWATI, RIYAMA; SANIAH, RATNA (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
Problem-solving skills in the learning process play an important role in enhancing the ability to find ways or solutions to achieve a goal, such as solving math problems. This study aims to investigate the impact of the ROLEM model on students' mathematical problem-solving abilities by considering students' self-efficacy. Additionally, this study explores the influence of self-efficacy on students' mathematical problem-solving abilities and the combined impact of the ROLEM model and self-efficacy on students' mathematical problem-solving abilities. This quantitative research examines students' mathematical problem-solving abilities by applying the ROLEM learning model and self-efficacy as a control. The subjects of this study were 60 high school students, with 30 students learning using the ROLEM model and 30 students using the discovery learning model. The data collection tools consisted of a self-efficacy questionnaire with 20 statements and a mathematical problem-solving essay test with 5 questions. Data analysis used one-way ANCOVA. The hypothesis test results showed that the ROLEM model influences mathematical problem-solving abilities when students' self-efficacy is controlled. Additionally, self-efficacy as a covariate variable also affects students' mathematical problem-solving abilities. Together, the ROLEM model and self-efficacy have an impact on students' mathematical problem-solving abilities. ABSTRAKKemampuan pemecahan masalah dalam proses pembelajaran memiliki peran penting dalam meningkatkan kemampuan mencari cara atau solusi terhadap suatu masalah yang ingin dicapai misalkan dalam menyelesaikan soal matematika. Penelitian ini bertujuan untuk menyelidiki dampak model ROLEM terhadap kemampuan pemecahan masalah matematis siswa dengan mempertimbangkan self-efficacy siswa. Selain itu, penelitian ini juga mengeksplorasi pengaruh self-efficacy terhadap kemampuan pemecahan masalah matematis siswa, serta dampak gabungan model ROLEM dan self-efficacy terhadap kemampuan pemecahan masalah matematis siswa. Penelitian ini berjenis kuantitatif yang mengkaji kemampuan pemecahan masalah matematis siswa dengan menerapkan model pembelajaran ROLEM dan self-efficacy sebagai pengontrol. Subjek penelitian ini berjumlah 60 siswa SMA, dengan rincian 30 siswa belajar menggunakan ROLEM dan 30 siswa menggunakan model discovery learning. Alat yang digunakan untuk mengumpulkan data terdiri dari angket self-efficacy yang berjumlah 20 pernyataan dan tes uraian kemampuan pemecahan masalah yang berjumlah 5 pertanyaan. Analisis data yang digunakan one-way ancova. Hasil uji hipotesis menunjukkan bahwa model ROLEM berpengaruh terhadap kemampuan pemecahan masalah matematis saat self-efficacy siswa dikontrol. Selain itu, self-efficacy sebagai variabel kovariat juga mempengaruhi kemampuan pemecahan masalah matematis siswa. Secara bersamaan, model ROLEM dan self-efficacy memiliki pengaruh terhadap kemampuan pemecahan masalah matematis siswa.